2021
DOI: 10.6007/ijarbss/v11-i4/9040
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Intention to Purchase Fraudulent Honey among Malaysian Consumers

Abstract: This paper aims to assess consumer awareness about fraudulent honey and its impact on purchase intention using an extended Theory of Planned Behaviour model. An online questionnaire survey was administered among honey consumers in Malaysia. Multiple regression analysis was employed on the 289-obtained-data to generate the relationship between awareness, attitude, subjective norms, perceived behavioural control, and consumers' intention to purchase fraudulent honey. Findings show that attitude and perceived beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…Konsumen membeli madu palsu karena memiliki harga lebih murah dibandingkan madu asli serta lebih mudah didapatkan. Konsumen madu di Malaysia memiliki kesadaran terhadap madu palsu, tetapi tidak memengaruhi perilaku pembelian madu palsu [10].…”
Section: Hubungan Persepsi Manfaat Kesehatan Dengan Perilaku Pembelia...unclassified
See 1 more Smart Citation
“…Konsumen membeli madu palsu karena memiliki harga lebih murah dibandingkan madu asli serta lebih mudah didapatkan. Konsumen madu di Malaysia memiliki kesadaran terhadap madu palsu, tetapi tidak memengaruhi perilaku pembelian madu palsu [10].…”
Section: Hubungan Persepsi Manfaat Kesehatan Dengan Perilaku Pembelia...unclassified
“…Manfaat kesehatan merupakan hal terpenting yang dipertimbangkan oleh konsumen untuk mengonsumsi madu dengan tujuan medis [9]. Persepsi kontrol perilaku secara signifikan berhubungan positif terhadap niat konsumsi madu palsu [10]. Sikap merupakan penentu utama dari terbentuknya niat yang selanjutnya menjadi sebuah perilaku, tetapi persepsi kontrol perilaku dapat secara langsung membentuk perilaku tanpa terbentuknya niat [11].…”
unclassified
“…As part of a study conducted by Fairchild et al (2003) it was found that there is an increasing need among consumers to learn more about the origin and processes undergone by the food products, honey included. Ahmad et al (2021) point out that consumers are aware of the existence of the adulterated honey market and, still, some of them choose to buy and consume it. This is due to the consumption needs of this segment of consumers that favour fake honey since it has a lower price and it is available in almost any store or supermarket (Ahmad et al, 2021).…”
Section: Consumer Perception Of Honey Quality and Adulterationmentioning
confidence: 99%
“…Ahmad et al (2021) point out that consumers are aware of the existence of the adulterated honey market and, still, some of them choose to buy and consume it. This is due to the consumption needs of this segment of consumers that favour fake honey since it has a lower price and it is available in almost any store or supermarket (Ahmad et al, 2021). Accordingly, even if consumers are knowledgeable of the presence of adulterated honey on the market, this does not affect their intention of buying it (Ahmad et al, 2021).…”
Section: Consumer Perception Of Honey Quality and Adulterationmentioning
confidence: 99%
See 1 more Smart Citation